The difference in the conjugation of one of the two verbs beginning with the present tense in some of them and one of them (Journal of the College of Basic Education, 2023)
Grammarians differed as to the permissibility of merging one of the two verbs beginning with the verb present orIts inadmissibility. The source of the dispute is the validity of this confusion among some readers, and IbnMalik validated his statement by saying:And Aflak and Adaghm greeted without cautionIbn Aqil represented him in (Atjali).It is also the way it unfolds and hidesAs for Ari Sebawayh, it was stated in his saying ((If the two met, you would speak and shield yourself.You have the choice, if you wish to affirm them, or if you wish to omit one of them:Glorified be He: ((The angels descend upon them ((, (1)) and ((their sides move away from their beds)) (2)If you wish, I omitted the second ta'. Confirming that is His saying, the Blessed and Exalted: (The angels and the Spirit descend in it.((, (3) and his saying ((And you used to long for death)) (4) … and they do not live in this Ta in ((You speak))And so on... (((5).As for the other disagreement in the like: ((you remember)) ((you remember)) and ((you orphan))((Teammon)) ((Tattolon)) ((Tattolon)) ..etc.Some of them said to delete the first, and they are the Kufans, and some of them said to delete the second, and they areBasrans.The ninety are in the book ((Al-Insaf fi Masa'il al-Khalaf)).